2016
DOI: 10.1016/j.jocn.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of acute multifocal placoid pigment epitheliopathy

Abstract: Acute multifocal placoid pigment epitheliopathy (AMPPE) is an autoimmune chorioretinal disease that can be complicated by neurological involvement. There is limited information on this potentially treatable condition in the neurological literature. The objective of this patient series is to describe the neurological complications of AMPPE. We retrospectively identified patients with neurological complications of AMPPE seen at Auckland Hospital between 2008 and 2013 and summarised cases in the literature betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 4 , 5 Rarely, cerebral vasculitis, and even death may occur. 5 , 6 , 7 Here, we present a novel association of APMPPE and isolated CN III palsy in a 20-year-old woman.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“… 4 , 5 Rarely, cerebral vasculitis, and even death may occur. 5 , 6 , 7 Here, we present a novel association of APMPPE and isolated CN III palsy in a 20-year-old woman.…”
Section: Introductionmentioning
confidence: 82%
“… 6 Brownlee et al identified five patients with neurological complications of AMPPE seen at Auckland Hospital between 2008 and 2013, and summarised cases in the literature between 1976 and 2013. 7 Published complications most commonly include cerebral vasculitis and stroke, but have also been known to include headaches, meningoencephalitis, viral meningitis, seizures, peripheral neuropathy, CN VI palsy, transient hearing loss, cavernous sinus thrombosis, hypoesthesia & paresthesia. 6 , 7 CNS complications were observed to occur twice as often in men, and may occur simultaneously with ocular symptoms or months later, 6 , 7 , 13 with two thirds of ischemic events occurring within 4 weeks of visual symptom onset.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations